Perception of students on entrepreneurship education - Iklima Husna Abdul Rahim; Dzulkifli Mukhtar (Center for Promoting Ideas (CPI), USA, 2021)
Universities play an important role in helping to boost the Malaysian economy through entrepreneurship education. Entrepreneurship education has been created by the government to expose students to career opportunities in business. The government's efforts are to help reduce the problem of unemployment that graduates face after they graduate. This is because the difficulty of finding a job is a problem for the country as the percentage of unemployment among graduate’s increases every year. Therefore, this study was conducted to examine students' perceptions of entrepreneurship education in shaping entrepreneurial intention. Students' perceptions of entrepreneurship education are measured based on three variables: entrepreneurial curriculum, teaching methods, and university’s role. The study design is a survey study where data is collected through the distribution of questionnaire forms. The questionnaire that was distributed is in the form of closed-ended questions with a 5-point Likert scale. A total of 114 students pursuing a Bachelor of Business (Entrepreneurship) degree were selected through the purposive sampling method. The study data were analysed using Statistical Package for Social Science (SPSS) software version 23.0. The findings of the study show that the entrepreneurial curriculum and teaching methods indicated a significant relationship with entrepreneurial intentions. However, the university’s role variable showed opposite results, that is, no significant relationship with entrepreneurial intentions. In conclusion, the curriculum in entrepreneurship education and teaching methods by the lecturers can help enhance the students' intention to venture into entrepreneurship. The results of this study are expected to assist universities and governments in improving entrepreneurship education in Malaysian universities.